Volatile Compound Fingerprints of Black Cumin (Nigella sativa L.) Seed Oil Extracted by Supercritical Carbon Dioxide - Winatta Sakdasri; Buntita Sakulkittiyut; Somkiat Ngamprasertsith; Ruengwit Sawangkeaw (My University, 2021)
Black cumin (Nigella sativa L.) seed oil consists of many volatile oils dissolved in the fixed oil. In this work, the seed oil samples were obtained from supercritical CO2 (SCCO2) extraction under various pressures (20.0–30.0 MPa) and temperatures (40–60 °C). The volatile compound fingerprints of SCCO2-extracted oils were analyzed by static headspace-gas chromatography (SH-GC-FID) without using any organic solvent. The comparison of volatile compound fingerprints of SCCO2 and n-hexane extracts was compared with the direct analysis of milled seed.
Keywords: Supercritical Carbon Dioxide; Nigella sativa; Hexane; Supercritical fluid extraction; Thymoquinone; Nigella sativa pharmacological applications